1998
DOI: 10.1017/s0889189300007815
|View full text |Cite
|
Sign up to set email alerts
|

Soil Improvement Following Addition of Chipped Wood from Twigs

Abstract: Wood residues are applied to soils to improve their organic matter content and related biological, physical, and chemical properties. We monitored the changes in soil total C and N content, the bacterial, fungal and actinomycetal populations, and microbial biomass and activity during 20 weeks in the first season following the application of chipped wood from twigs (CWT), and as residual effects during the second growing season on a loamy soil (coarse loamy, mixed, frigid, Humic Fragiorthod) in Sainte-Brigitte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
3
17
0
4
Order By: Relevance
“…2). These results confirmed previous findings that addition of wood-based residues can stimulate soil microbial activity (Elkins et al 1984;Zibilske 1987;Tardif 1996;Lalande et al 1998). In our study, the amounts of FDA hydrolyzed ranged from 30 to 100 mg kg -1 of dry soil h -1 .…”
Section: Impact Of De-inking Paper Sludge On Enzyme Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…2). These results confirmed previous findings that addition of wood-based residues can stimulate soil microbial activity (Elkins et al 1984;Zibilske 1987;Tardif 1996;Lalande et al 1998). In our study, the amounts of FDA hydrolyzed ranged from 30 to 100 mg kg -1 of dry soil h -1 .…”
Section: Impact Of De-inking Paper Sludge On Enzyme Activitysupporting
confidence: 92%
“…Several studies have reported that incorporation of woodbased residues in soil promotes microbial growth and activity (Elkins et al 1984;Zibilske 1987;Lalande et al 1998), but little attention has been paid to DPS. This material has large C to N and C to P ratios, and its incorporation to the soil generally results in net N and P immobilization (Fierro et al 1997).…”
Section: Canadian Journal Of Soil Sciencementioning
confidence: 99%
“…and stimulate soil microbial communities due to the addition of organic matter (Lalande et al, 1998;Olsen and Gounder, 2001;Ozores-Hampton, 1998). Possible disadvantages of organic mulches include nutrient tie-up and lowering of soil temperatures to sub-optimum levels (Hill et al, 1982;Schonbeck and Evanylo, 1998).…”
Section: Research Reportsmentioning
confidence: 99%
“…However, the addition of organic compounds, such as plant residues, manures, composts and biosolids, produces major benefits to soil properties and fertility (Cabral et al 1998;Lalande et al 1998;Bipfubusa et al 2005), and the resulting impact on soil acidification could then be regarded as less important than the increase in the organic matter content. Continuous application of N fertilizers, such as ammonium nitrate, ammonium sulphate and urea, also results in an increase in soil acidity.…”
mentioning
confidence: 99%